2013
DOI: 10.1111/mpp.12025
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cis‐acting P1 protein and translational elements on the expression of Potato virus Y helper‐component proteinase (HCPro) in heterologous systems and its suppression of silencing activity

Abstract: In the Potyvirus genus, the P1 protein is the first N-terminal product processed from the viral polyprotein, followed by the helper-component proteinase (HCPro). In silencing suppression patch assays, we found that Potato virus Y (PVY) HCPro expressed from a P1-HCPro sequence increased the accumulation of a reporter gene, whereas protein expressed from an HCPro sequence did not, even with P1 supplied in trans. This enhancing effect of P1 has been noted in other potyviruses, but has remained unexplained. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 52 publications
1
25
3
Order By: Relevance
“…Surprisingly, we found that both P1N‐PISPO and P1 are RNA silencing suppressors in SPFMV. Intrinsic silencing suppression has not been described previously for P1 proteins of potyviruses (Rajamäki et al ., ; Tena Fernández et al ., ), nor was it found herein for P1 of SPLV (which clusters as an immediate outgroup to the SPFMV group). Most recent reports assign potyvirus P1 a role for increasing the accumulation of HCpro and consequently enhancing its silencing activity (Tena Fernández et al ., ).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Surprisingly, we found that both P1N‐PISPO and P1 are RNA silencing suppressors in SPFMV. Intrinsic silencing suppression has not been described previously for P1 proteins of potyviruses (Rajamäki et al ., ; Tena Fernández et al ., ), nor was it found herein for P1 of SPLV (which clusters as an immediate outgroup to the SPFMV group). Most recent reports assign potyvirus P1 a role for increasing the accumulation of HCpro and consequently enhancing its silencing activity (Tena Fernández et al ., ).…”
Section: Discussioncontrasting
confidence: 71%
“…Intrinsic silencing suppression has not been described previously for P1 proteins of potyviruses (Rajamäki et al ., ; Tena Fernández et al ., ), nor was it found herein for P1 of SPLV (which clusters as an immediate outgroup to the SPFMV group). Most recent reports assign potyvirus P1 a role for increasing the accumulation of HCpro and consequently enhancing its silencing activity (Tena Fernández et al ., ). We also showed that P1 and P1N‐PISPO seem to have different silencing activities in SPFMV, a strategy described for different RSS proteins of other viruses as well (Lu et al ., ; Senshu et al ., ).…”
Section: Discussioncontrasting
confidence: 71%
“…In this regard, for instance, the VPg of the potyvirus PVA has been found to counteract RNA silencing (46,61). Additionally, the levels of expression of HCPro in other potyviruses were reported to be regulated by P1 (62). In the case of SPFMV, although our transient agroinfiltration experiments with individual gene products showed no clear antisilencing activity for P1 or HCPro, preliminary results suggest that P1-HCPro might display some activity.…”
Section: Discussioncontrasting
confidence: 43%
“…The primer pairs used to amplify all these genes are available upon request. Viral proteins were analyzed by Western blotting as described by Tena et al (33). T7-tagged P25 was detected with horseradish peroxidase (HRP)-conjugated anti-T7 antibody (Novagen) (1:5,000 dilution).…”
Section: Binarymentioning
confidence: 99%